Codeswitching in the Classroom (Taylor & Francis, 2023)
Bringing together sociolinguistic, linguistic, and educational perspectives, this cutting‐edge overview of codeswitching examines language mixing in teaching and learning in bilingual classrooms. As interest in pedagogical applications of bilingual language mixing increases, so too does a need for a thorough discussion of the topic. This volume serves that need by providing an original and wide-ranging discussion of theoretical, pedagogical, and policy‐related issues and obstacles in classroom settings—the pedagogical consequences of codeswitching for teaching and learning of language and content in one‐way and two‐way bilingual classrooms. Part I provides an introduction to (socio)linguistic and pedagogical contributions to scholarship in the field, both historical and contemporary. Part II focuses on codeswitching in teaching and learning, and addresses a range of pedagogical challenges to language mixing in a variety of contexts, such as literacy and mathematics instruction. Part III looks at language ideology and language policy to explore how students navigate educational spaces and negotiate their identities in the face of competing language ideologies and assumptions. This volume breaks new ground and serves as an important contribution on codeswitching for scholars, researchers, and teacher educators of language education, multilingualism, and applied linguistics.